A participatory scenario analysis of potential small-scale farming systems in rural Thaba Nchu and Emmaus regions of South Africa - V.N. Mathinya; A.C. Franke; G.W.J. van de Ven; K.E. Giller (Social Sciences and Humanities Open)
Despite substantial government investments, small-scale farming in South Africa has largely failed to deliver anticipated improvements in rural livelihoods. This has led to growing skepticism about its role in rural development strategies. This study investigated context-specific small-scale farming systems in two contrasting communal areas: semi-arid Thaba Nchu and sub-humid Emmaus. We applied a two-step approach: (1) desktop analysis to propose biophysically and economically feasible systems and (2) participatory scenario planning with farmers to evaluate their plausibility and social acceptability. In Thaba Nchu, the proposed systems included weaner production, feeder lambs, piggery, poultry (broilers), and lucerne cropping. In Emmaus, they included piggery, poultry, lucerne cropping, vegetable production, and agroforestry with macadamia nuts. Although lucerne in Thaba Nchu and broilers in Emmaus showed the highest potential contributions to household living income, socio-economic constraints limited their adoption. In Thaba Nchu, internal conflicts over common property resources hindered collective livestock systems. In Emmaus, land allocation preferences for staple crops reduced the likelihood of adopting alternative cash crops. Our findings highlight the need to address governance challenges related to common property resource management and land tenure security. Social acceptability and cooperation are critical preconditions for successful small-scale farming interventions. This study contributes to rural development discourse by identifying the conditions under which small-scale farming can complement broader livelihood strategies and support national development goals.